GAMBARAN PERILAKU TENAGA KESEHATAN TERHADAP PELAYANAN PRIMA DI PUSKESMAS TOMUAN KECAMATAN SIANTAR TIMUR KOTA PEMATANGSIANTAR TAHUN 2012 - doan moreno; Lita andayani; Eddy Syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2013)
ABSTRACTExcellent service is a service that satisfies customer, a service that overshots service standard or equal to standard, and a best service. This research aims to see the description of behavior of the health officers to the excellence service in Puskesmas Tomuan in 2012.This research is descriptive with quantitative approach. The results were analyzed descriptively and quantitatively described as a percentage. Number of samples to be interviewed were 25 respondents.Results showed most respondents are female as much as 92,0%. The majority of repondents’ age are 31-36 years old. Most respondents’ education are D3 and the majority of respondents work for 1-4, 5-8, and 17-20 years each as much as 24,0%. The knowledge of health officers are moderate category as much as 76,0%. The attitudes of health officers are good category as much as 96,0% and the action of all health officers are good.Expected to puskesmas management need by undertaking been increased management which well to equipment and available facility at puskesmas. Besides on duty local health needs to arrange training and excellence service socialization to puskesmas officer to upgrade service to puskesmas visitor.